Cladribine prolongs progression-free survival and time to second treatment compared to fludarabine and high-dose chlorambucil in chronic lymphocytic leukemia. Issue 12 (December 2014) - Mulligan, Stephen P.; Karlsson, Karin; Strömberg, Mats; Jønsson, Viggo; Gill, Devinder; Hammerström, Jens; Hertzberg, Mark; McLennan, Roger; Uggla, Bertil; Norman, John; Wallvik, Jonas; Sundström, Gunnel; et al.
Abstract We conducted a randomized phase III trial to compare the efficacy and safety of two purine analogs, cladribine and fludarabine, with high-dose chlorambucil, in patients with previously untreated chronic lymphocytic leukemia (CLL). Between 1997 and 2004, 223 patients with CLL were randomly assigned to cladribine, fludarabine or chlorambucil, for six cycles of therapy with frequent health-related quality of life assessments. There was no statistical difference for the primary endpoint of overall response with cladribine (70%), fludarabine (67%) and chlorambucil (59%), or complete remission (12%, 7% and 8%), respectively. However, the median progression-free survival (25, 10, 9 months) and median time to second treatment (40, 22, 21 months) were superior with cladribine. There was no significant difference in overall survival (96, 82 and 91 months), nor in toxicity or HRQoL assessments. Monotherapy with cladribine gives superior PFS and longer response duration than fludarabine and chlorambucil as first-line treatment of CLL.